2012
DOI: 10.1111/j.1540-6210.2012.02649.x
|View full text |Cite
|
Sign up to set email alerts
|

Building Ethical Capital: Perceptions of Ethical Climate in the Public Sector

Abstract: Th is article examines infl uences on public servant perceptions of ethical climate in the public sector. Th e array of benefi cial outcomes produced by perceptions of a positive ethical climate, the existence of government programs aimed at improving ethical climate, and implications for government accountability and trustworthiness all argue for a better understanding of the sources of these perceptions. Empirical analyses of survey responses from employees of the U.S. federal executive branch show that indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 65 publications
(71 reference statements)
1
24
0
1
Order By: Relevance
“…We This subscale also had a strong positive correlation with the ethical culture measure, whereas other dimensions had small or insignificant correlations (Treviño et al, 1998). In addition, we included in our analysis other ethical culture or ethical climate (ethical culture, hereafter) measures that were similar to Treviño et al's scale (Babin, Boles, & Robin, 2000;Hunt et al, 1989;Menzel, 1995;Raile, 2013;Schwepker, 2001).…”
Section: Inclusion Criteriamentioning
confidence: 99%
“…We This subscale also had a strong positive correlation with the ethical culture measure, whereas other dimensions had small or insignificant correlations (Treviño et al, 1998). In addition, we included in our analysis other ethical culture or ethical climate (ethical culture, hereafter) measures that were similar to Treviño et al's scale (Babin, Boles, & Robin, 2000;Hunt et al, 1989;Menzel, 1995;Raile, 2013;Schwepker, 2001).…”
Section: Inclusion Criteriamentioning
confidence: 99%
“…It is interesting that the statement "A legal framework adequately determines public servant standards of behaviour" did not even correlate with one statement in terms of the ethical climate. Th is is converse to the conclusions made by Bowman and Knox (2008) and Afedize (2015) and, to some extent, the research of Rasmussen et al (2003) and Raile (2013). At the same time, the statements in relation to the ethical climate that are oriented towards "individualism" do not correlate with infrastructure.…”
Section: Co-ordinating Bodymentioning
confidence: 36%
“…Th ey found that public servant ethical climates are externally determined by professional or legal norms. Similarly, Raile (2013) suggests that "public servant perceptions of ethical climate have predictable sources. " He pointed out that public administrators can simultaneously help shape ethical-climate perception.…”
Section: Ethical Climates In Public Administrationmentioning
confidence: 99%
See 1 more Smart Citation
“…PendahuluanPada dasarnya fungsi etika pada pengembangan organisasi tidak hanya berfokus pada perilaku individu dalam bekerja, tetapi juga dalam hal lainnya seperti perilaku pengambilan keputusan (Wyld dan Jones, 2007). Sejauh mana pemerintah yang bersifat demokratis dapat memenuhi tujuan melayani rakyat dan meningkatkan kesejahteraan umum sebagian besar sangat bergantung pada sikap dan perilaku dari pegawai publik (Raile, 2012). Oleh karena itu dengan mengeksplorasi iklim etika di ranah organisasi pemerintah akan membantu administrator maupun pembuat kebijakan dalam memahami sifat perilaku etis dalam pengaturan organisasi publik dan bagaimana kondisi ini dapat mempengaruhi pelaksanaan kebijakan publik dan berikut sikap dan perilaku individu (Rasmussen et al, 2003).Fokus kepada etika sektor publik dipandang sebagai reaksi atas tren baru dari manajemen publik (Stensota, 2010).…”
unclassified